Aplikasi Monitoring Kesuburan Tanaman Hias Mawar menggunakan Arduino - Valerie Caroline Alverina; Leo Willyanto Santoso; Handry Khoswanto (Jurnal Infra, 2020)
Society in general uses plants as decoration for all types of places such as hotels, restaurants, to residential homes. But each plant needs its own care so that plants can last long. One of the plants commonly used as decoration is the rose plant. Sometimes people are overwhelmed in caring for roses such as forgetting to water plants, watering for rose plants is lacking or excessive. Many studies have used Arduino to monitor rose plants but cannot be controlled mobile.The use of smartphones is now also increasing in the community, it will greatly facilitate the user if monitoring of plants can be done on smartphones. The plant watering system uses Arduino which is connected to the internet and the Blynk server. By using the Blynk server, you can connect Arduino with a smartphone, making it easier for users to control and monitor rose plants such as watering and fertilizing as well as seeing the condition of roses from a distance and can help the growth of roses. The result of this study are the system can treat and monitor roses according to parameter, which is soil moisture 70% - 80%, fertilizing, monitoring temperature 18 ºC - 26ºC and soil pH 5.5 - 7.0.